2012
DOI: 10.1017/s1751731111001522
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chronic immune system stimulation models in growing pigs

Abstract: Two experiments (EXPs) were conducted to evaluate models of immune system stimulation (ISS) that can be used in nutrient metabolism studies in growing pigs. In EXP I, the pig's immune response to three non-pathogenic immunogens was evaluated, whereas in EXP II the pig's more general response to one of the immunogens was contrasted with observations on non-ISS pigs. In EXP I, nine growing barrows were fitted with a jugular catheter, and after recovery assigned to one of three treatments. Three immunogens were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 37 publications
7
54
0
Order By: Relevance
“…Interestingly, there was a strong negative correlation between TNF-α and IL-1β concentrations in serum, indicating that LPS-induced immune system stimulation may primarily activate TNF-α rather than IL-1β. However, previous studies showed increased production of both TNF-α and IL-1β after LPS challenge in pigs (Wright et al, 2000;Rakhshandeh and de Lange, 2012). The serotype of E. coli LPS, sampling timing, and dose rate of LPS might have influenced serum concentrations of cytokines and immunity-related molecules, as the response of pigs to LPS was reported to be dose dependent (Webel et al, 1997).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Interestingly, there was a strong negative correlation between TNF-α and IL-1β concentrations in serum, indicating that LPS-induced immune system stimulation may primarily activate TNF-α rather than IL-1β. However, previous studies showed increased production of both TNF-α and IL-1β after LPS challenge in pigs (Wright et al, 2000;Rakhshandeh and de Lange, 2012). The serotype of E. coli LPS, sampling timing, and dose rate of LPS might have influenced serum concentrations of cytokines and immunity-related molecules, as the response of pigs to LPS was reported to be dose dependent (Webel et al, 1997).…”
Section: Discussionmentioning
confidence: 97%
“…Disease challenge, whether it is clinical or subclinical, under commercial conditions of pig production can lead to the production of numerous immune system-related compounds such as acute phase proteins (Wright et al, 2000) and cytokines (Curfs et al, 1997;Paradis et al, 2012;Rakhshandeh and de Lange, 2012;Rakhshandeh et al, 2014). The increased release of proinflammatory cytokines in immune system-challenged pigs causes reduced feed intake and growth performance and deterioration in feed efficiency, mainly due to altered nutrient partitioning and neurological infection responses such as anorexia and fever (Webel et al, 1997;Kim et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations